Investigating Students’ Listening Problems in EFL Learning - Eva Meidi Kulsum; Alfikri Hidayatullah (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this study is to investigate students’ listening problems in an English as a Foreign Langauge (EFL) learning. It is conducted in one of private Junior High School in Purwakarta. This research is categorized as qualitative research by conducting a semi structured interview as the instruments of this research. The interview guideline was adopted from the categorization of listening problems from of Trismasari, et al., (2016). 8 students were selected as particapant of this reserch using purposive sampling technique and adjusted to the criteria of students with low level of listening skills. In reason that this type of students is considered as students who experienced high level of listening difficulties. Based on the data found, the researcher concluded that students encounter various kinds of listening problems in learning comprehension such as lack of listening ability, limited english vocabulary, poor knowledge of grammar, listening strategies, linguistic knowledge, familiarity with the topic, rate of speech, the inability to concentrate, different accent and dialect, and environmental variables. By knowing the problem encountered by students in listening comprehension, it is hoped that this research can provide useful insights into learners‘ performance on the listening comprehension test and its relation to listening problems. Besides, the finding of this research can also be used by the teacher on how to make enjoyable listening activities in language classroom.